PERUBAHAN KARAKTERISTIK ELEKTROMAGNETIK MENGGUNAKAN METODE GROUND PENETRATING RADAR HUBUNGANNYA DENGAN KARAKTERISTIK SEDIMEN BAWAH PERMUKAAN - -, Andi Agus Nur (Bulletin of Scientific Contribution, 2007)
Ground Penetrating Radar one of a Geophysics methods with principally to elektromagnetics wave reflection which is caused by changes of electromagnetics characteristics (contrast of material dielectric) in subsurface. The product data is a 2D profil that interpreted later from configuration reflection pattern on data to determine type of the sediment.